2016
DOI: 10.1124/dmd.115.066803
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epoxide-Derived Metabolite(s) of Benzbromarone

Abstract: Benzbromarone (BBR) is a benzofuran derivative that has been quite useful for the treatment of gout; however, it was withdrawn from European markets in 2003 because of reported serious incidents of drug-induced liver injury. BBR-induced hepatotoxicity has been suggested to be associated with the formation of a quinone intermediate. The present study reported epoxide-derived intermediate(s) of BBR. An N-acetylcysteine (NAC) conjugate derived from epoxide metabolite(s) was detected in both microsomal incubations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 29 publications
7
40
0
Order By: Relevance
“…McDonald and Rettie (2007) first suggested that BBR was sequentially oxidized by CYP2C9 to a catechol which can be further oxidized to a reactive o-quinone intermediate identified as glutathione (GSH) conjugates in liver microsomal systems. Previous work from our laboratory revealed that BBR was metabolized to an epoxide intermediate(s) through the initial epoxidation of the benzofuran ring by CYP3A (Wang et al, 2016b). In our following studies, mercapturic acid excreted from urine and hepatic protein adduction derived from the epoxide intermediate (s) were observed in BBR-treated mice, which confirmed the epoxidation metabolism of BBR in vivo (Wang et al, 2016a,b).…”
Section: Introductionsupporting
confidence: 85%
“…McDonald and Rettie (2007) first suggested that BBR was sequentially oxidized by CYP2C9 to a catechol which can be further oxidized to a reactive o-quinone intermediate identified as glutathione (GSH) conjugates in liver microsomal systems. Previous work from our laboratory revealed that BBR was metabolized to an epoxide intermediate(s) through the initial epoxidation of the benzofuran ring by CYP3A (Wang et al, 2016b). In our following studies, mercapturic acid excreted from urine and hepatic protein adduction derived from the epoxide intermediate (s) were observed in BBR-treated mice, which confirmed the epoxidation metabolism of BBR in vivo (Wang et al, 2016a,b).…”
Section: Introductionsupporting
confidence: 85%
“…The observation of a high volume of protein adduction derived from BBR, combined with the finding of more potent hepatotoxicity induced by BBR, led us to propose that epoxidation at C6 of BBR is a key step for hepatotoxicity of BBR. Our previous study demonstrated that the reaction of the epoxide metabolite(s) of BBR with GSH contributes to the depletion of GSH (Wang et al, 2016b). The present study found that treatment of BBR caused significant elevation in serum AST activity in opposition to a decrease in hepatic and plasma GSH content.…”
Section: Discussionsupporting
confidence: 56%
“…Liver tissues (0.2 g) harvested 30 minutes postadministration were homogenized in 2.0 ml of phosphate buffer (pH 7.4). The resulting homogenates were denatured by heating in a water bath at 60°C for 30 minutes and then digested overnight with a mixture of chymotrypsin (1.0 mg/ml) and Pronase E (2.0 mg/ml), according to our previous study (Wang et al, 2016b). The supernatants (5 ml) were subjected to the LC-MS/MS system for analysis.…”
Section: Determination Of In Vivo Protein Adductions Derived From Bbrmentioning
confidence: 99%
“…The final metabolite of this molecule is ortho-quinone, which may be related to hepatotoxicity [43]. Other studies have reported the presence of an intermediate epoxide metabolite, which has been demonstrated to be hepatotoxic in murine models [44,45]. Another study reported that the addition of a fluorine molecule in the 6 position of benzbromarone reduced the production of these metabolites, reducing its toxicity in mice [46].…”
Section: A Mechanism For Hepatotoxicity: Animal Models and In Vitro Smentioning
confidence: 99%